Interceptive orthodontic management of occlusal problems resulting from ankylosed second primary molars. Case Report - Valverde Montalva, Hernán Renzo (2022)
Ankylosis is a dental anomaly of unknown etiology that causes bone bridges between the root cement and the alveolar bone that can lead to different dental problems. The objective of this case report is to present interceptive orthodontic treatment for a class I malocclusion in a 7-year-old boy. This treatment was proposed considering that the patient presented incomplete first phase mixed dentition and the clinical absence of teeth 55, 85, 16 and 46. Two ankylosed deciduous teeth were extracted and the occlusal face of the permanent teeth was operculectomy. The headgear was used in the maxilla and the labioactive plate or lip Bumper in the mandible, which made it possible to recover the space lost for the correct eruption of the permanent pieces. Early intervention through treatment allows partial correction of the malocclusion and prevents the problem from worsening.